Stereochemical Geometries and Photoluminescence in Pseudo-Halido-Zinc(II) Complexes. Structural Comparison between the Corresponding Cadmium(II) Analogs - Franz A. Mautner; Roland C. Fischer; Ana Torvisco; Nahed M. H. Salem; Amber R. Dugas; Shelby F. Aaron; Sushant P. Sahu; Febee R. Louka; Salah S. Massoud (Inorganics, 2021)
Six pseudohalide zinc(II) containing a variety of N-donor auxiliary amines were structurally characterized. These include two mononuclear trigonal bipyramidal [Zn(NTB)(N3)]ClO4·½H2O (3) and [Zn(TPA)(NCS)]ClO4 (4), two distorted octahedral [Zn(1,8-damnph)2(dca)2] (5) and [Zn(8-amq)2(dca)2] (6a) as well as two 1D polymeric chains catena-[Zn(isq)2(μ1,5-dca)2] (7) and catena-[Zn(N,N-Me2en)2(μ1,5-dca)]dca (8), where NTB = tris(2-benzimidazolylmethyl)amine, TPA = tris(2-pyridylmethyl)amine, 1,8-damnph = 1,8-diaminonaphthalene, 8-amq = 8-amino-quinoline, isq = isoquinoline (isq) and N,N-Me2en = N,N-dimethylethylenediamine. In general, with the exception of 6 and 8, the complexes exhibited luminescence emission in MeOH associated with red shift of the emission maxima, and the strongest visible fluorescence peak was detected at 421 nm (λex = 330 nm) in the case of Complex 5.